Efektivitas Atraktan Terhadap Aktivitas Elaeidobius Kamerunicus untuk Meningkatkan Produksi Kelapa Sawit - Hanjaya Hanjaya; Astuti, Yohana Th. Maria; Valensi Kautsar (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
This study aims to examine the effectiveness of attractants on the activity of the pollinating beetle Elaeidobius kamerunicus and its impact on the efficiency of pollination and palm oil (Elaeis guineensis) production at PT Menthobi Makmur Lestari, Lamandau Regency, Central Kalimantan. The study was conducted from May to July 2025 using a factorial randomized block design with two factors: topography (flat 0–8% and hilly 15–25%) and attractant doses (0, 1, 2, and 3 ml/ha) with three replications.The parameters observed included the frequency of E. kamerunicus visits to female flowers and the percentage of fruit set. The results showed that the topography factor, attractant dose, and their interaction significantly affected the number of E. kamerunicus visits and fruit set (p < 0.01). The combination of flat land with high attractant doses resulted in the highest visits (69.04 beetles/spike) and maximum fruit set (75.11%), while the hilly land without attractants showed the lowest results (34.60 beetles/spike; 61.22%). The application of attractants increased fruit set by more than 20% compared to the control, leading to an increase in bunch weight (BJR) of approximately 5.67 kg/bunch, additional production of about 1,151 kg FFB/ha per 1.5 months, and a potential income of Rp 3,683,200/ha, far exceeding the application cost of Rp 211,638/ha. These results indicate that the use of attractants is an effective and efficient agronomic strategy to improve palm oil productivity. Thus, attractants have proven to significantly enhance pollination efficiency and palm oil production, providing substantial economic benefits to farmers and supporting the sustainability of palm oil plantations. This approach offers an applicable and sustainable solution for agricultural practices, which can be applied to various locations with similar topographical conditions.